Analisis Dampak Alokasi Dana Desa (ADD) Terhadap Pemberdayaan Masyarakat dan Kelembagaan Desa - Rulyanti Susi Wardhani; Vebtasvili Vebtasvili; Kelvin Frans Surbakti (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The aim of this research is to analyze the management of village fund allocation at the Planning, Implementation, Administration, Reporting and Accountability stages and to analyze the impact of village fund allocation on community empowerment and village institutions in Mangkol Village and Pedindang Village, Pangkalan Baru District, Central Bangka Regency. His research is a type of qualitative research and the data used is primary data and secondary data collected using observation, interviews and documentation methods. Resource persons in the research consisted of the Village Head, Village Secretary, Village Treasurer, BPD Management, PKK, LPM, BUMDes, Karang Taruna, RT, Community. The data analysis technique used in the field is tennis The results of this research show that the Planning, Implementation, Administration, Reporting and Accountability stages are in accordance with the predetermined pathways and guidelines. Village Fund Allocation has a positive impact on community empowerment and village institutions. However, the community has not been able to develop the economy in the village due to a lack of responsibility and understanding from the BUMDes management team.